1992
DOI: 10.1200/jco.1992.10.12.1889
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of iodine 131 metaiodobenzylguanidine in chemoresistant neuroblastoma: a United Kingdom Children's Cancer Study Group investigation.

Abstract: This study has established an effective method of activity prescription that predicts subsequent toxicity, with the maximally tolerated dose being sufficient activity to deliver a whole-body-absorbed radiation dose of 2.5 Gy. The objective response rate is comparable to other single agents in chemoresistant neuroblastoma and suggests that 131I mIBG may be a useful method for targeting radiotherapy in metastatic neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 15 publications
4
65
3
Order By: Relevance
“…Initial phase I-II studies with 131 I-MIBG therapy, dating back to the late 1980s, showed good tolerance and demonstrated objective tumour responses in 20-60% of patients failing to respond to modern therapies (Italian MIBG Workshop, 1987;Schwabe et al, 1987;Klingebiel et al, 1989;Lashford et al, 1992). In addition, significant pain relief was noticed even in patients who did not exhibit objective responses (Klingebiel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial phase I-II studies with 131 I-MIBG therapy, dating back to the late 1980s, showed good tolerance and demonstrated objective tumour responses in 20-60% of patients failing to respond to modern therapies (Italian MIBG Workshop, 1987;Schwabe et al, 1987;Klingebiel et al, 1989;Lashford et al, 1992). In addition, significant pain relief was noticed even in patients who did not exhibit objective responses (Klingebiel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given at higher doses 131 I-MIBG has proven to be active against these tumours, especially neuroblastoma (Schwabe et al, 1987;Klingebiel et al, 1989). Most clinical studies have been carried out on patients in advanced stages of the neoplasia (Italian MIBG Workshop, 1987;Klingebiel et al, 1989;Lashford et al, 1992), although recently 131 I-MIBG has been administered to poorrisk patients as up-front therapy in an attempt to improve their outcome (Mastrangelo et al, 1993(Mastrangelo et al, , 1998Weber et al, 1996).…”
mentioning
confidence: 99%
“…3 Radioiodinated MIBG can be used for imaging 4,5 as well as targeted radiotherapy. 6,7 Early studies of patients with recurrent or refractory neuroblastoma treated with 131 I MIBG have been encouraging, 8 but it appears unlikely that 131 I MIBG used alone will be curative. MIBG is a small molecule which penetrates multicellular tumor spheroids and probably tumors more readily than antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of neuroblastoma tumors are MIBG-avid, and infusions of 131 I-MIBG allow for the targeted delivery of radiation therapy directly to any sites of active disease. Initial studies showed overall response rates of 21-47% in patients with neuroblastoma [114][115][116], and subsequent studies have used ASCR after MIBG treatment, allowing for the administration of higher radiation doses. In a large phase II study, 164 patients with relapsed or refractory neuroblastoma were treated with 131 I-MIBG.…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%